2023
DOI: 10.1093/plphys/kiad335
|View full text |Cite
|
Sign up to set email alerts
|

TurboID reveals the proxiomes of Chlamydomonas proteins involved in thylakoid biogenesis and stress response

Elena Kreis,
Katharina König,
Melissa Misir
et al.

Abstract: In Chlamydomonas (Chlamydomonas reinhardtii) the VESICLE-INDUCING PROTEINS IN PLASTIDS 1 and 2 (VIPP1 and VIPP2) play roles in the sensing and coping with membrane stress and in thylakoid membrane biogenesis. To gain more insight into these processes, we aimed to identify proteins interacting with VIPP1/2 in the chloroplast and chose proximity labeling (PL) for this purpose. We used the transient interaction between the nucleotide exchange factor CHLOROPLAST GRPE HOMOLOG 1 (CGE1) and the stromal HEAT SHOCK PRO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 131 publications
(280 reference statements)
0
1
0
Order By: Relevance
“…Recently, protein-protein interactions have been deduced by proximity labeling, a technique that uses a genetically encoded biotin ligase fused to a protein of interest (interaction bait) that brings the ligase to its partner proteins that become biotinylated (Zhang, Li, et al, 2022). The use of proximity labeling in Chlamydomonas is nascent but has already established a pyrenoid interactome (Lau et al, 2023) and identified interactions of CGE1 and VIPP1/2 (Kreis et al, 2023) under oxidative stress (H 2 O 2 ) conditions with HSP70B, CDJ2, and proteins involved in the regulation of thylakoid biogenesis and photosynthetic electron transport.…”
Section: Proxim It Y L Abelingmentioning
confidence: 99%
“…Recently, protein-protein interactions have been deduced by proximity labeling, a technique that uses a genetically encoded biotin ligase fused to a protein of interest (interaction bait) that brings the ligase to its partner proteins that become biotinylated (Zhang, Li, et al, 2022). The use of proximity labeling in Chlamydomonas is nascent but has already established a pyrenoid interactome (Lau et al, 2023) and identified interactions of CGE1 and VIPP1/2 (Kreis et al, 2023) under oxidative stress (H 2 O 2 ) conditions with HSP70B, CDJ2, and proteins involved in the regulation of thylakoid biogenesis and photosynthetic electron transport.…”
Section: Proxim It Y L Abelingmentioning
confidence: 99%